Adaption and Memory: The Reckless Leader and The Effects of the First Family (European Journal of Behavioral Sciences, 2020)
There are harmful leaders, but too few instances of how harmful the leadership is within the church get explored and how it affects the first families. Several harmful leadership styles, such as an egotistical leader, an ignorant leader, and a reckless leader, studied in some capacity under leadership.  There is an ideology put forward, and it is believed that leaders are not just appearing in business or corporate America, but leaders are leaders and are showing forth their leadership in everyday instances as a mother who teaches their child. The leader's leadership scope was explored by filtering it through adaption and memory, with memory being a significant part of this paper. The overall platform is looking at (reckless) leadership through the lens of religion (Christianity) with a philosophical undertone using personal reflections. The results for this research, under the assumption, of using the qualitative method and using two qualitative designs, helped with data collection. The narrative approach and the phenomenological approach show the leader's evolving behavior and the first family's behavior through personal observation with testimonies to expose the effects of their memory. Scriptures are used to expose or reveal the split leadership dynamic and how memory dictates leaders' response and behavior.  Two individual stories were rendered, which more participants are needed to develop a consensus of adaption and memory in leadership and how it affects the first family. Understanding that some things are caught, and some things are taught, this study's outcome, by looking at leadership and the effects of the first family, concluding with the suggestion of furthering this research to explore a more in-depth understanding of reckless leadership in the scope of adaptation to memory.